2011
DOI: 10.1186/1754-9493-5-17
|View full text |Cite
|
Sign up to set email alerts
|

Failure of fixation of trochanteric femur fractures: Clinical recommendations for avoiding Z-effect and reverse Z-effect type complications

Abstract: BackgroundZ-effect and reverse Z-effect are complications that arise from the surgical treatment of pertrochanteric fractures of the femur with proximal femoral nails (PFN) comprising two interlocking head screws. Such complications are induced by the migration of screws in opposite directions, which may lead to failure of the osteosynthesis.FindingsThe paper describes three cases of pertrochanteric fractures that were treated with PFN with two interlocking screws that evolved to either Z-effect or reverse Z-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 8 publications
(15 reference statements)
0
36
0
Order By: Relevance
“…With second-generation nails, which have two hip screws, backup of one screw and movement of the other screw in the opposite direction, called the "Z" effect, were sometimes observed for reasons that are unclear. This phenomenon usually results in cutout of the screws [9][10][11]21]. To overcome this disadvantage of second-generation nails, third-generation nails with solitary hip units that feature the characteristics of hip screws and antirotation screws have been launched on the market.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With second-generation nails, which have two hip screws, backup of one screw and movement of the other screw in the opposite direction, called the "Z" effect, were sometimes observed for reasons that are unclear. This phenomenon usually results in cutout of the screws [9][10][11]21]. To overcome this disadvantage of second-generation nails, third-generation nails with solitary hip units that feature the characteristics of hip screws and antirotation screws have been launched on the market.…”
Section: Discussionmentioning
confidence: 98%
“…This situation may lead to collapse in the fracture area and reverse displacement of the proximal locking screw. Another major problem, seen especially with second-generation nails with two proximal lag screws, is the "Z" effect, which is basically the migration of one lag screw into the coxofemoral joint as the other screw migrates in the reverse direction [9][10][11]. To address this complication, third-generation nails that provide more solid fixation in osteoporotic bone and prevent rotation of the head and neck fragment via a modified screw or blade design have been developed.…”
Section: Introductionmentioning
confidence: 98%
“…It has also been suggested that medial cortical comminution leads to exacerbation of the phenomenon leading to severe fixation failure. Additionally poor bone quality and incorrect entry point have been implicated as causative factors [37]. Various clinical case series and reports have been published but the actual incidence of the phenomenon is unclear since it is mainly reported when it leads to failure of the fixation [37][38][39].…”
Section: Z-effect and Central Migrationmentioning
confidence: 97%
“…Additionally poor bone quality and incorrect entry point have been implicated as causative factors [37]. Various clinical case series and reports have been published but the actual incidence of the phenomenon is unclear since it is mainly reported when it leads to failure of the fixation [37][38][39]. Implant designs with static locking mechanism of both of the proximal interlocking screws have been developed in order to prevent this complication.…”
Section: Z-effect and Central Migrationmentioning
confidence: 98%
“…we have encountered 'Z' effect in 5 (6.7%), reverse 'Z' effect in 2 (2.7%) , Cut out of the antirotational screw in 3 (4.05%) , Antirotational screw breakage in 1 (1.6%) , Non union in 1(1.6%) and, Failure to put distal screw in 1 (1.6%). The cause of Z effect and reverse Z-effects is not properly understood but the probable cause is due to fracture fixed in varus position, severe medial comminution, inappropriate entry point of the nail , poor bone quality 22 leading to differential compression & tensioning of two screws . Migration of the screws due to severe osteoporosis was detected during the follow up in 7 patients .…”
Section: IVmentioning
confidence: 99%